A Comparative Study of Colorectal Cancer Based on Patient’s Age - Dhahir, Nasir K.; Noaman, Aqeel Abbas (Journal of the Faculty of Medicine Baghdad, 2021)
Abstract:Background: The alteration of bowel habits, bleeding per-rectum and anemia were common features in both groups in this study, but in young patients there was a delay of 6 months between the presenting symptoms and the definitive diagnosis because the disease was not suspected and investigated in them. The most common site for the tumors in young patients was the rectum and in patients above the age of 40 years was the Sigmoid.The pathological finding showed that classification of the colorectal tumors in young patients appear moderately to poorly differentiated adenocarcinoma , this indicate a more malignant course of the disease in young patients.This study send a message to all clinicians that the incidence of colorectal cancer is increasing in young patients and therefore we should be alert when dealing with young patients presenting with abdominal pain, bleeding per-rectum and alteration of bowel habit to diagnose the disease at an early stage to undertake curative surgery .Aim of the study: To study the clinical coarse of colorectal cancer in age between (less than 40 to above 40), and the most frequent site and distribution, and the types of surgical intervention.Patients and methods: In the period between January 2012 to March 2013, 35 patients with colorectal cancer were treated at Al-Yarmouk Hospital,10 patients were below the age of 40 years ,( 5 Males and 5 Females ) with age ranging from 22-40 years , 25 patients were above the age of 40 years (12 males and13 females).Results:100% of patients less than 40 years presenting as anemia and 50% bleeding per rectum, while 88% of patients above 40 years with weakness and lethargy.30% of patients less 40years age, and 36% of patients above 40 years consider as an emergency cases, and others as elective cases. Surgical treatment involving 50% of patients less than 40 are right, left hemicolectomy and anterior resection, and in age of above 40 56% by left hemicolectomy. More common stages in young patents are  C and B  but in old  A ,B , C.Recommendations: Researchers recommend periodic screening by a doctor to diagnose the tumor early with the need to develop educational programs on early signs of colorectal cancer.